Selfish learning: The impact of self-referential encoding on children's literacy attainment. (December 2015) - Turk, David J.; Gillespie-Smith, Karri; Krigolson, Olave E.; Havard, Catriona; Conway, Martin A.; Cunningham, Sheila J.
Abstract: Self-referencing (i.e., thinking about oneself during encoding) can increase attention toward to-be-encoded material, and support memory for information in adults and children. The current inquiry tested an educational application of this 'self reference effect' (SRE) on memory. A self-referential modification of literacy tasks (vocabulary spelling) was tested in two experiments. In Experiment 1, seven-to nine-year-old children ( N  = 47) were asked to learn the spelling of four nonsense words by copying the vocabulary and generating sentences. Half of the children were asked to include themselves as a subject in each sentence. Results showed that children in this self-referent condition produced longer sentences and increased spelling accuracy by more than 20%, relative to those in an other-referent condition. Experiment 2 ( N  = 32) replicated this pattern in real-word learning. These findings demonstrate the significant potential advantages of utilizing self-referential encoding in the classroom. Highlights: Thinking about oneself (self-referencing) during encoding improves memory. Literacy tasks can be adapted to include self-referential instructions. Two experiments assessed learning advantages of self-referential spelling tasks. Data confirmed a significant learning enhancement for self over other-referencing. Findings suggest that self-referencing should be applied across teaching materials.